2014
DOI: 10.1165/rcmb.2013-0452oc
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemia Potentiates Airway Responsiveness to Parasympathetic Nerve Stimulation in Obese Rats

Abstract: Obesity is a substantial risk factor for developing asthma, but the molecular mechanisms underlying this relationship are unclear. We tested the role of insulin in airway responsiveness to nerve stimulation using rats genetically prone or resistant to diet-induced obesity. Airway response to vagus nerve stimulation and airway M 2 and M 3 muscarinic receptor function were measured in obeseprone and -resistant rats with high or low circulating insulin. The effects of insulin on nerve-mediated human airway smooth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 51 publications
(74 reference statements)
3
66
0
2
Order By: Relevance
“…Conversely, a combination of fluticasone/salmeterol yielded greater improvements in asthma outcomes in comparison with montelukast over a range of BMIs [7]. Recently published experimental studies have suggested that metabolic changes induced by high-fat fed obese mice result in increased parasympathetic activity, which results in an increase of acetylcholine levels in the lungs, thus producing AHR [19,31]. These findings highlight the possible use of the antimuscarinics as adjuvant drugs in the treatment of asthma in obese subjects.…”
Section: Asthma Control In Obesitymentioning
confidence: 95%
“…Conversely, a combination of fluticasone/salmeterol yielded greater improvements in asthma outcomes in comparison with montelukast over a range of BMIs [7]. Recently published experimental studies have suggested that metabolic changes induced by high-fat fed obese mice result in increased parasympathetic activity, which results in an increase of acetylcholine levels in the lungs, thus producing AHR [19,31]. These findings highlight the possible use of the antimuscarinics as adjuvant drugs in the treatment of asthma in obese subjects.…”
Section: Asthma Control In Obesitymentioning
confidence: 95%
“…129 Insulin resistance also increases free insulin-like growth factor, which is associated with ASM proliferation. 130 Furthermore, insulin may increase airway hyperresponsiveness by modulating parasympathetic stimulation, studied in an obese 131 These studies suggest that insulin resistance and associated hyperinsulinemia influence ASM cell function through different mechanisms, with the end result of increased bronchial hyperresponsiveness. Translational studies are now needed to study the role of each of these pathways in ASM cells obtained from obese asthmatics.…”
Section: Association With Insulin Resistancementioning
confidence: 99%
“…Data from animal models suggest that there are changes in the neurological control of airway smooth muscle tone through cholinergic signaling pathways in obesity (25)(26)(27). High insulin levels are present in some obese humans, and high insulin levels can increase vagal-induced bronchoconstriction both through peripheral effects on acetylcholine release (25) and through centrally mediated effects on vagal signaling (26). Leptin, an adipokine increased in obesity, can also affect the parasympathetic regulation of airway tone (27).…”
Section: Asthma Caused By Obesitymentioning
confidence: 99%
“…Clinical studies to date have not specifically targeted the late-onset asthma of obesity. Animal studies demonstrating that cholinergic signaling affects airway tone (25)(26)(27) suggest that focused studies targeting insulin resistance and/or cholinergic pathways in the lateonset asthma of obesity associated with little overt inflammation might be worthwhile.…”
Section: Asthma Caused By Obesitymentioning
confidence: 99%